NUANSA SUFISTIK TAFSĪR FIRDAUS AL-NA‘ĪM KARYA KH TAIFUR ALIWAFA - Ismegawati Ismegawati (Faculty of Ushuluddin UIN Syarif Hidayatullah Jakarta, 2018)
This paper discusses the Sufistic nuances of Tafsīr Firdaus al-Na’īm by KH. Taifur Aliwafa. Using the descriptive-analytic method, this literature study answers the question how the author of this tafsir book interprets verses relating to aspects of Sufism, with the case of love verses. This study found that the author of this tafsir in interpreting the verses was influenced by his educational background, where he was trained in the Naqsyabandiyah Ṭarīqa tradition from his position as a student to his position as a murshid.